2001
DOI: 10.1093/rheumatology/40.5.579
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular variability in childhood periodic fever with hyperimmunoglobulinaemia D

Abstract: Most HIDS patients have mutations in the MVK gene. The clinical variability observed cannot be explained by genotypic differences. Periodic fever and elevated IgD can result from other, still unknown, causes. Hence, testing for MK deficiency is necessary in patients with unexplained periodic fever.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 13 publications
0
55
0
2
Order By: Relevance
“…Combining the results obtained in our laboratory with the data in the international HIDS registry 8 (A Simon, personal communication), we observed that of the 34 Dutch HIDS patients analysed thus far, only four did not carry the V377I allele. 11,12,20,21 Three patients were found to be homozygotes for V377I, 11,12,20,21 , two of whom have been confirmed by analysis of parental DNA. Twenty-seven patients were compound heterozygotes for the V377I allele.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…Combining the results obtained in our laboratory with the data in the international HIDS registry 8 (A Simon, personal communication), we observed that of the 34 Dutch HIDS patients analysed thus far, only four did not carry the V377I allele. 11,12,20,21 Three patients were found to be homozygotes for V377I, 11,12,20,21 , two of whom have been confirmed by analysis of parental DNA. Twenty-seven patients were compound heterozygotes for the V377I allele.…”
Section: Resultsmentioning
confidence: 84%
“…The second allele in the majority of these patients was one that has been identified also in MA, including the allele H20P (59A4C, seven patients) and the allele I268T (803T4C, nine patients). 11,12,20,21 In addition to these HIDS patients, five Dutch MA patients have been analysed. Four of these were heterozygotes for the A334T (1000G4A) allele, and one patient was homozygous for I268T.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This HIDS subgroup, termed variant-type HIDS, is characterized by normal or only slightly decreased MK activities (9,10). Given the phenotypic similarities, variant-type HIDS raises two important questions: 1) are there HIDS-related mutations in genes other than MVK?…”
Section: Objective To Describe Biochemical Findings and The Spectrummentioning
confidence: 99%